Persepsi Nasabah terhadap Aplikasi M-Banking pada Bank Swasta dan Bank Pemerintah - Wangsanegara, Johan Ivander; Susilawati, Cicilia Erna; Kristyanto, Visi Saujaningati (Ekonomis: Journal of Economics and Business, 2024)
Information and communication technology has revolutionized the banking sector and at its peak during the Covid 19 pandemic, most transactions can be carried out without the need to visit a bank and using mobile banking applications. In Indonesia, there are two banks that are most popular in using m-banking, m-BCA which is managed by a private bank and Livin by Mandiri which is managed by a state-owned company. The aim of this research is to analyze whether there are differences of trust, service quality and perceived risk on customer satisfaction in private and government managed m-Banking. The research method uses a quantitative approach based on data collected through online surveys. There are 180 active m-Banking customers with generation Z and Millennial demographics, students and productive workers. The results show that the factors that influence customer satisfaction in using m-Banking lie in the aspects of service quality and trust, while perceived risk has no effect. Furthermore, differences in the influence of m-banking application service quality determine customer satisfaction. Where, m-BCA customers are relatively more satisfied because the service is in accordance with the promises, transaction speed, security, attractive visual appearance, the application is more responsive and easier than the Livin by Mandiri. For generation Z and millennials, the use of digital banking applications is more influenced by the application's ability to meet transaction needs rather than threat factors such as the speed of computing personal data, cyber-crime and bank system errors.